1993
DOI: 10.3354/meps101067
|View full text |Cite
|
Sign up to set email alerts
|

Vertical distribution and migration of fish larvae in a Northeast Pacific bay

Abstract: Fish larvae were collected at 6 depths in Auke Bay, southeastern Alaska, USA, on 4 days in May and June 1987. On 3 dates samples were collected between 08:OO and 13:00 h, on the other date samples were collected every 4 h during 24 h. Vertical distributions of light, temperature, salinity, chlorophyll and copepod nauplii were also measured. Wind speed data were available from a nearby station. Smelt (Osmeridae) larvae, the most abundant larval fish taxon, migrated to the surface at midnight, whereas walleye po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
1
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 18 publications
0
12
1
1
Order By: Relevance
“…In some studies, vertlcal migratory behaviour has been linked to the vertical distribution of prey (Fortier & Leggett 1983, Munk et al 1989, Neilson & Perry 1990, Haldorson et al 1993; however, in a number of species, including S. punctafa in this study, no relationship could be found between diurnal ascenl/nocturnal diffusion and prey distribution (Yamashita et al 1985, Brewer & Kleppel 1986, Lyczkowski-Shultz & Steen 1991. Because fish larvae are visual feeders (Blaxter 1986), the migratory behaviour observed in many species might simply be a response to finding optimum light levels for detection of prey.…”
Section: Daycontrasting
confidence: 43%
See 2 more Smart Citations
“…In some studies, vertlcal migratory behaviour has been linked to the vertical distribution of prey (Fortier & Leggett 1983, Munk et al 1989, Neilson & Perry 1990, Haldorson et al 1993; however, in a number of species, including S. punctafa in this study, no relationship could be found between diurnal ascenl/nocturnal diffusion and prey distribution (Yamashita et al 1985, Brewer & Kleppel 1986, Lyczkowski-Shultz & Steen 1991. Because fish larvae are visual feeders (Blaxter 1986), the migratory behaviour observed in many species might simply be a response to finding optimum light levels for detection of prey.…”
Section: Daycontrasting
confidence: 43%
“…Steen 1991), specifically, stratification near the surface during the day, and random distribution or 'nocturnal diffusion' at night (Brewer & Kleppel 1986, Davis et al 1990, Leis 1991, Haldorson et al 1993). All larvae collected in Port Phillip Bay were relatively large (15 to 20 mm) and competent to settle (Jenkins & May 1994).…”
Section: Daymentioning
confidence: 99%
See 1 more Smart Citation
“…There are marked ontogenetic and taxonomic differences in the vertical distribution patterns of most larval fish taxa (Cowen et al 1993;Haldorson et al 1993;Olivar and Sabates 1997). It has been suggested that the vertical distribution of larval fishes may be a result of taxon-specific preferred light levels (Blaxter 1988;Leis 1991a).…”
mentioning
confidence: 99%
“…Current velocity (Boehlert et al 1992), thermoclines (Haldorson et al 1993;Williams and Koslow 1997), and light intensity (Blaxter 1988;Leis 1991a) have all been suggested as key physical factors that structure the vertical distribution of fish larvae. The role of light intensity has been the focus of most research.…”
mentioning
confidence: 99%